White collar rhabdomyolysis with acute kidney injury - Bhakthavatsalam, R. K. (Indian J Nephrol, 2016)
Rhabdomyolysis is a clinical syndrome resulting from the disintegration of muscle cell and spillage of toxic intracellular contents into circulation. Strenuous, unaccustomed exercise leads to exertional rhabdomyolysis and cause AKI. We report a 26-year-old female who developed white collar rhabdomyolysis with AKI after performing sit-ups (Super Yoga Brain) for 108 times in temple. She was managed with hemodialysis and supporting therapy. She made a full recovery after 4 weeks. Awareness of this condition and early diagnosis is highlighted.